2017
DOI: 10.1002/adhm.201701154
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Nucleus as a Sensor of Cell Environment Topography

Abstract: The proper integration of biophysical cues from the cell vicinity is crucial for cells to maintain homeostasis, cooperate with other cells within the tissues, and properly fulfill their biological function. It is therefore crucial to fully understand how cells integrate these extracellular signals for tissue engineering and regenerative medicine. Topography has emerged as a prominent component of the cellular microenvironment that has pleiotropic effects on cell behavior. This progress report focuses on the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 215 publications
(299 reference statements)
2
37
0
Order By: Relevance
“…The surfaces of biomaterials play a central role in the modulation of cell behavior [42,43] and in mechanotransduction [7,44,45]. Topographical features have an influence on direct transmission of force, which causes a reorganization of the cytoskeleton [31,[46][47][48] and changes in cell shape to adapt to the underlying surface [44,49,50]. Furthermore, signaling pathways ultimately modulate cell proliferation and differentiation [4,5,8,10,46,[51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…The surfaces of biomaterials play a central role in the modulation of cell behavior [42,43] and in mechanotransduction [7,44,45]. Topographical features have an influence on direct transmission of force, which causes a reorganization of the cytoskeleton [31,[46][47][48] and changes in cell shape to adapt to the underlying surface [44,49,50]. Furthermore, signaling pathways ultimately modulate cell proliferation and differentiation [4,5,8,10,46,[51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Both nuclei distribution and F-actin orientation satisfy these criteria. Several studies establish nuclei as essential players of cell reaction to topography 38 . We demonstrated that single cells avoid crossing convex regions owing to the tendency of nuclei to slide away from convex curvature 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The important influence of geometrical constraints on the evolution and the equilibrium configurations is well accepted in the context of physical systems. The role of geometrical constraints to influence or even to guide biological processes is also starting to emerge [68][69][70][71][72]. In a biological context the role of geometrical constraints goes beyond what was explored for physical systems.…”
Section: Discussionmentioning
confidence: 99%